2021
DOI: 10.1111/medu.14562
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the drivers of medical student emigration intention across two African nations

Abstract: Background: Sub-Saharan Africa faces the highest relative need for health care workers in the world and the emigration of physicians significantly contributes to this deficit. Few studies have explored development of these patterns during medical education. This study investigates career aspirations of medical students in two African nations with similar Human Development Indices, but distinct differences in training structure to better inform retention strategies. Methods: A cross-sectional survey was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…For instance, in one study, it was found that 49.7% of Malagasy medical students and 25.2% of Tanzanian medical students expressed their intention to emigrate to practise. 18 Similarly, in another study, it was revealed that 44.6% of Ugandan medical students planned to emigrate. 19 It is interesting that the observed trends in these low-income and middle-income countries align with those in the UK, despite the latter’s significantly larger economy.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, in one study, it was found that 49.7% of Malagasy medical students and 25.2% of Tanzanian medical students expressed their intention to emigrate to practise. 18 Similarly, in another study, it was revealed that 44.6% of Ugandan medical students planned to emigrate. 19 It is interesting that the observed trends in these low-income and middle-income countries align with those in the UK, despite the latter’s significantly larger economy.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have examined the preference for overseas experiences among medical students from English-speaking high-income countries (HICs) and their attitudes toward IHEs. Students from low- or middle-income countries (LMICs) often pursue overseas careers in HICs because of better work conditions with higher income, larger capacity, and advanced training opportunities in those countries [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] However, many African medical schools lack robust research training infrastructure and opportunities [7][8][9] , which can be associated with greater likelihood of research-inclined medical trainees emigrating to high-income countries. 10 The Sub-Saharan African Medical School Study (SSAMSS) of >100 African institutions found that <10% of faculty members at most schools were involved in sponsored research, limiting knowledge generation, impeding recruitment and retention of talented faculty members, and harming student training. 11 SSAMSS researchers recommended improved funding for research and research training at African institutions to improve medical education and population health, while emphasizing need for creative solutions and international collaborations to overcome scarce institutional support.…”
Section: Introductionmentioning
confidence: 99%